Commentaries on Job, Hosea, Joel, and Amos - Julian, of Eclanum, Bishop., 380-approximately 455, author; (Robert Charles); the Venerable, Saint,.; of Gabala,. (Downers Grove, Ill. : : IVP Academic, 2021)
"In this ACT volume, Thomas Scheck provides a new translation of Julian of Eclanum's commentaries on Job, Hosea, Joel, and Amos. Gain insight into how early Christians read texts such as God's speech to Job, Hosea's symbolic representation of God's unending love for a faithless Israel, Joel's anticipation of the outpouring of the Holy Spirit, and Amos's call for social justice"-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Bible. -- Commentaries; Bible. -- Sermons; Bible. Job--Commentaries.; Bible. Hosea--Commentaries.; Bible. Joel--Commentaries.; Bible. Amos--Commentaries.